Enhancing Junior High School Students’ English Achievement through Educational Gamification: A Quasi-Experimental Study - Ismail, Ismail (Majesty Journal, 2023)
Educational gamification has increasingly been recognized as an innovative pedagogical strategy for improving students’ motivation, engagement, and learning achievement in English language classrooms. This study aimed to examine the impact of educational gamification on junior high school students’ academic achievement in learning English at SMPN 5 Enrekang, Indonesia. Employing a quasi-experimental design, the study involved 53 seventh-grade students divided into an experimental group and a control group. The experimental group was taught using gamification-based learning activities supported by ClassDojo and Breakout EDU, while the control group received conventional instruction. Data were collected through pre-test and post-test using the EF SET test, which measured students’ English reading and listening proficiency. The results showed that the two groups had relatively comparable pre-test scores, indicating similar initial English proficiency before the intervention. After the treatment, however, the experimental group achieved a higher mean post-test score than the control group. This finding suggests that educational gamification contributed positively to students’ English learning achievement by creating a more interactive, motivating, and engaging learning environment. The study highlights the pedagogical value of integrating game elements into English language instruction, particularly at the junior high school level. It also implies that teachers need to design technology-supported and student-centered learning activities to enhance students’ academic performance and classroom participation.